Khatmul Hadits Riyadhus Shalihin bil Hifzhi di Pondok Pesantren Wali Songo Situbondo - Umi Nuriyatur Rohmah; Hanief Monady; Muhammad Hasan Said Iderus (NALAR, 2023)
In Living Hadith Studies, there are three variants of traditions. There are written traditions, practical traditions, and oral traditions. The research talks about an oral tradition at Wali Songo Islamic Boarding School in Situbondo: Khatmul Hadith bil Hifzhi. It focuses on knowing the practice and interpretation of the rule of Khatmul Hadith. It is description research that systematically describes the practical of living hadith in Wali Songo Islamic Boarding School using a phenomenology approach with social action theory by Max Weber. The research concludes that, firstly, the Khatmul Hadith tradition is a practice of reading all of the hadiths in Riyadhus Shalihin by memorizing the hadith (bil hifzhi) and then reading the prays for the closure and also doing some discussions and questions about all around the interpretations of hadith from the boarding school caretakers. Secondly, the understanding of the Khatmul Hadith based on Maz Webers theory, there are four categories of the act, there is the traditional act as a form to conserve traditions of Meccas Islamic scholars, the affective action to show happiness when doing the discussions with the Caretakers and get good grades, the instrumentally rational act, as a practice of murajaah for the students, the values reasonable action, as for obtaining Allahs pleasures and the Prophets shariah, also receiving the blessings from the hadith readings.Keywords:Living hadith;Khatmul Hadith;Riyadhus Shalihin;Wali Songo Situbondo Islamic Boarding School